If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3s + 7)(s + 6) = 0 Reorder the terms: (7 + 3s)(s + 6) = 0 Reorder the terms: (7 + 3s)(6 + s) = 0 Multiply (7 + 3s) * (6 + s) (7(6 + s) + 3s * (6 + s)) = 0 ((6 * 7 + s * 7) + 3s * (6 + s)) = 0 ((42 + 7s) + 3s * (6 + s)) = 0 (42 + 7s + (6 * 3s + s * 3s)) = 0 (42 + 7s + (18s + 3s2)) = 0 Combine like terms: 7s + 18s = 25s (42 + 25s + 3s2) = 0 Solving 42 + 25s + 3s2 = 0 Solving for variable 's'. Factor a trinomial. (6 + s)(7 + 3s) = 0Subproblem 1
Set the factor '(6 + s)' equal to zero and attempt to solve: Simplifying 6 + s = 0 Solving 6 + s = 0 Move all terms containing s to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + s = 0 + -6 Combine like terms: 6 + -6 = 0 0 + s = 0 + -6 s = 0 + -6 Combine like terms: 0 + -6 = -6 s = -6 Simplifying s = -6Subproblem 2
Set the factor '(7 + 3s)' equal to zero and attempt to solve: Simplifying 7 + 3s = 0 Solving 7 + 3s = 0 Move all terms containing s to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3s = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3s = 0 + -7 3s = 0 + -7 Combine like terms: 0 + -7 = -7 3s = -7 Divide each side by '3'. s = -2.333333333 Simplifying s = -2.333333333Solution
s = {-6, -2.333333333}
| (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 | | 3(4y+5)=51 | | 6(2g-5)=-6 | | x^2+9=6x | | 8x+16=2x+106 | | 2y+10=5y-4 | | 14x^2=0 |